Numerical Simulation of Tsunami During the Earthquake in the Philippines 02.12.2023 - Mazova Raisa; Polyakov Kirill; Kurkin Andrey (Russian Journal of Earth Sciences)
In this paper numerical simulation of tsunami waves is carried out using data from the earthquake off the coast of Mindanao Island in the Philippine Sea on 23 December 2023 in the western part of the Pacific Ocean. The paper considers two scenarios of seismic source localization with different dynamics of the Earth's crust displacement in the seismic source region during the earthquake process. Consideration of two scenarios with different location of keyboard blocks, into which the earthquake source is segmented, allows one to study the influence of source geometry on the characteristics of generated tsunami waves. In the course of simulation, during dynamic displacement of keyboard blocks in the earthquake source, tsunami source formation, tsunami waves and their propagation in the Pacific Ocean water area take place. The wave characteristics of the process along the mainland and island zones in the considered water area were obtained. The results of simulation for the two scenarios are compared with observational data, which makes it possible to identify which type of block arrangement provides better similarity with the recorded tsunami characteristics and, therefore, better describes the real dynamics of the earthquake source.